Winter activity patterns of American martens ( Martes americana): rejection of the hypothesis of thermal-cost minimization - Drew, Gary S.; Bissonette, John A. (Canadian Journal of Zoology, 1997)
Despite their temperate to subarctic geographic range, American martens (Martes americana) possess a thermally inefficient morphology. The lack of morphological adaptations for reducing thermal costs suggests that marten may use behavioral strategies to optimize thermal budgets. During the winters of 1989–1990 and 1990–1991, we radio-collared and monitored the diel activity of 7 martens. A log-linear model suggested that the presence or absence of light was the only factor associated with marten activity patterns (p < 0.001). A regression of the percentage of active fixes on ambient temperature failed to detect an association (b = −4.45, p = 0.084, n = 12). Contents of marten scats suggested that their activity was consistent with the prey-vulnerability hypothesis. While martens must balance multiple life requisites, their activity patterns suggest that they accept increased thermal costs in order to increase foraging efficiency. However, the nocturnal activity of martens during winter was also consistent with the hypothesis that they may be able to limit their own exposure to predation risk. The nocturnal habits of Newfoundland martens in the winter were consistent with the hypothesis of avoidance of predation risk.